And when we've run out of cruise missiles, we've got plenty of these little babies - Hubris missile for Clinton, 1999 - Pryor, Geoff, 1944- (1999)
NATO launches airstrikes on Serbia during the war on Kosovo to get President Milosevic's forces to withdraw . US President Clinton is no doubt hoping a show of Western might will draw the conflict to a speedy conclusion.--Information provided by Geoff Pryor.
Title devised by cataloguer from information provided on image.
Part of the Pryor collection of cartoons and drawings.
Published in the Canberra Times on 3rd April 1999.
Also available online
Keywords: Politicians -- Caricatures and cartoons